2003
DOI: 10.1128/iai.71.9.5087-5096.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pathogenicity Island Integrated Adjacent to the thrW tRNA Gene of Avian Pathogenic Escherichia coli Encodes a Vacuolating Autotransporter Toxin

Abstract: We report the complete nucleotide sequence and genetic organization of the Vat-encoding pathogenicity island (PAI) of avian pathogenic Escherichia coli strain Ec222. The 22,139-bp PAI is situated adjacent to the 3 terminus of the thrW tRNA gene, has a G؉C content of 41.2%, and includes a bacteriophage SfII integrase gene, mobile genetic elements, two open reading frames with products exhibiting sequence similarity to known proteins, and several other open reading frames of unknown function. The PAI encodes an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
113
0
10

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(130 citation statements)
references
References 45 publications
7
113
0
10
Order By: Relevance
“…According to the χ 2 test, the observed insertions are significant at P=0.01 level, which proved that tRNA gene loci are the insertion hotspots in the genome of Prochlorococcus. Our results confirm, from a statistical perspective, many earlier observations in prokaryotes (Reiter et al, 1989;Parreira and Gyles, 2003;van Aartsen, 2008). This previous work has revealed that tRNA loci are not only central components in translation, but also commonly serve as insertion sites for mobile elements in bacteria because there is an attB (bacterial attachment site) within some tRNA genes such as Arg and Pro (Reiter et al, 1989;Semsey et al, 2002), and therefore, the presence of these tRNA genes gives rise to variable genomic regions and the observed divergence of Prochlorococcus genomes.…”
Section: Trna As An Insertion Hotspotsupporting
confidence: 79%
“…According to the χ 2 test, the observed insertions are significant at P=0.01 level, which proved that tRNA gene loci are the insertion hotspots in the genome of Prochlorococcus. Our results confirm, from a statistical perspective, many earlier observations in prokaryotes (Reiter et al, 1989;Parreira and Gyles, 2003;van Aartsen, 2008). This previous work has revealed that tRNA loci are not only central components in translation, but also commonly serve as insertion sites for mobile elements in bacteria because there is an attB (bacterial attachment site) within some tRNA genes such as Arg and Pro (Reiter et al, 1989;Semsey et al, 2002), and therefore, the presence of these tRNA genes gives rise to variable genomic regions and the observed divergence of Prochlorococcus genomes.…”
Section: Trna As An Insertion Hotspotsupporting
confidence: 79%
“…Challenge studies indicated a significant reduction of the virulence of the ibeA mutant. Based on prevalence studies and virulence attenuation of a mutant, conclusions have been drawn for several of the virulence genes identified to date for APEC strains (Blanco et al, 1997;Delicato et al, 2003;Dozois et al, 1992Dozois et al, , 2000Parreira & Gyles, 2003). It is therefore reasonable to assume that ibeA, when present, plays a role in the pathogenicity of APEC strains.…”
Section: Discussionmentioning
confidence: 99%
“…Gene inactivation studies confirmed a role in the pathogenicity of APEC for the F1 (type 1) and P fimbrial adhesins (Dozois et al, 1992(Dozois et al, , 1996La Ragione et al, 2000a, b;Marc et al, 1998;Pourbakhsh et al, 1997), for the K1-antigen mediating resistance to phagocytosis (Mellata et al, 2003a), for the aerobactin high-affinity iron transport system (Lafont et al, 1987) and for the temperature-sensitive haemagglutinin Tsh (Dozois et al, 2000;Provence & Curtiss, 1994). Recently, Parreira & Gyles (2003) showed that a vacuolating toxin, Vat, was involved in the virulence of an APEC isolate. Another gene whose precise function remains to be elucidated is the iss gene (Binns et al, 1979); this gene is presumed to play a role in serum resistance but, if so, its role seems to be minor (Mellata et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few reports demonstrating that E. coli strains isolated from avian can produce toxins (Tsuji et al 1990, Blanco et al 1997a, Parreira et al 1998, Salvatori et al 2001, Parreira & Gyles, 2003. None of the isolates analyzed here possessed the genes that encoded toxins LT, STa, STb, Stx1, Stx2, Hly or CNF.…”
Section: Discussionmentioning
confidence: 89%